Komunikasi Antar Pribadi Terhadap Kinerja Karyawan Divisi Pemasaran PT Hamri Indonesia - Hemalya Yunnisa; Mochammad Mirza; Ajeng Pradesti (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
A part or department within a company called the marketing division is responsible for managing all aspects related to the marketing of the company's products or services. The marketing division also plays a crucial role in the development of a company, so it must perform well. Ability to communicate effectively and well is crucial for smooth interactions and activities, especially in formal settings. Because of this, the purpose of this study is to understand the interpersonal communication relationships inside PT Hamri Indonesia's marketing division. Additionally, it looks into how much interpersonal communication might help staff members in PT Hamri Indonesia's marketing division work better. Furthermore, the study attempts to pinpoint obstacles that PT Hamri Indonesia's marketing division faces in relation to interpersonal communication. Primary data for this study came from observations and interviews, and data analysis in this study is qualitative. The sources of secondary data include definitions, theories, and a variety of literary works. The importance of encouraging effective interpersonal communication among persons is indicated by the conclusion reached from the impact of interpersonal communication on the performance of marketing division employees.